There will be bodies - Davis, Lindsey (A Flavia Albia novel, 2025)
"A decade after the destructive eruption, Flavia Albia finds herself investigating family secrets and possible crimes buried in the ash of Mount Vesuvius. In first century Rome, Flavia Albia-daughter and successor to Marcus Didius Falco-is once again faced with uncovering the truth. Quite literally. Only ten year's previous, Mount Vesuvius erupted and rained ash down about the Roman cities and towns along the Bay of Naples. But while some cities were destroyed, others were merely badly damaged. And the uncle of Flavia Albia's husband seizes the opportunity to buy a villa...cheap! It just has to be dug out of the ash, and restored. Oh, and any bodies uncovered, including the previous owner, given a proper burial. And as the Villa is being renovated, there are indeed bodies found. But one is not like the others-instead of buried in the ash, the previous owner's body is found in a locked storeroom and Albia is immediately suspicious that he didn't die in the eruption. With suspicious caretakers, a large inheritance, untrustworthy friends and a Sicilian pirate sniffing around, Albia must solve the riddle of a long ago death, maybe murder, to prevent another one"--